EFEKTIVITAS PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) TERHADAP PELAKSANAAN KANTIN SEHAT DI SD NEGERI 4 MADE LAMONGAN - Arbiyanti, Marelsa Giswara; Nurdiana, Ratna; Eryadini, Ninies (STIE Atma Bhakti, 2025)
School Operational Assistance (BOS) is a program used to provide funding for non-personal operating costs for public and private education units. SD Negeri 4 Made began to make improvements, especially in terms of facilities and infrastructure to realize a healthy canteen at school. This study adopts a qualitative research type with the research objective of knowing the effectiveness of the management of BOS funds from the government to support the development of facilities and infrastructure that leads to planning and budgeting, implementation and administration, to reporting and accountability of BOS funds at SD Negeri 4 Made Lamongan. This research can be categorized as descriptive research, because it aims to describe the specific characteristics of a phenomenon and tries to describe and interpret what exists. The data collection methods used were observation, in-depth interviews and documentation. The results of the study showed that the use of BOS Funds at SD Negeri 4 Made Lamongan was effective because the BOS Funds received had been used to achieve educational goals at the school and were used for the development of school facilities and infrastructure, especially in the implementation of a healthy canteen. This was reinforced by the results of the observation that the Sd Negeri Made 4 Lamongan Canteen experienced significant development of facilities and infrastructure and reached the standard of a healthy canteen.